James Tilghman correspondence - Tilghman, James
ALsS (1829 January 23 and 27) written by Tilghman to Henry I. Williams regarding the sale of timber along the Susquehanna River in Pennsylvania.
Businessman of Baltimore, Md.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Williams, Henry I. -- Correspondence; Lumber trade -- Pennsylvania; Susquehanna River; Businessmen